Are prophylactic adjunctive macrolides efficacious against caesarean section surgical site infection: A systematic review and meta-analysis. (January 2020) - Farmer, Nicola; Hodgetts-Morton, Victoria; Morris, Rachel K.
Abstract: Surgical site infection (SSI) post- caesarean section (CS) remains high, prophylactic adjunctive macrolides may reduce this. This systematic review and meta-analysis evaluated whether adjunctive prophylactic macrolides administered at CS reduce the risk of endometritis and wound infection. MEDLINE, EMBASE, CINHAL and the Cochrane library were searched from inception to July-2018. Observational and randomised studies investigating women undergoing a CS receiving standard prophylactic antibiotics, adjunctive prophylactic macrolides and assessed any SSI outcome was included. Data was double-extracted. Studies were included in a meta-analysis if the same study design and SSI outcome was used. Risk ratios were calculated and heterogeneity was assessed using the I 2 test. Five studies were included in the systematic review and four in the meta-analysis. Two RCT's ( n  = 2610) found that macrolides significantly reduce the risk of wound infection RR [0.34; 95 %, 0.22 0.53] P = 0.00001 and endometritis RR [0.66; 95 %, 0.52, 0.85] P = 0.001 with no evidence of heterogeneity (I 2  = 0 %). Two cohort studies ( n  = 13, 809) found that azithromycin significantly reduces the risk of endometritis RR [0.16; 95 %, 0.04–0.62] P = 0.008, however significant heterogeneity was seen. Macrolides significantly reduce the risk of endometritis and wound infection post-CS. An effectiveness evaluation of post-cord clamping administration is needed to eliminate fetal antibiotic exposure and the long term infant implications this may have.